2019
DOI: 10.1016/j.cmi.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

European all-cause excess and influenza-attributable mortality in the 2017/18 season: should the burden of influenza B be reconsidered?

Abstract: Objectives: Weekly monitoring of European all-cause excess mortality, the EuroMOMO network, observed high excess mortality during the influenza B/Yamagata dominated 2017/18 winter season, especially among elderly. We describe all-cause excess and influenza-attributable mortality during the season 2017/18 in Europe. Methods: Based on weekly reporting of mortality from 24 European countries or sub-national regions, representing 60% of the European population excluding the Russian and Turkish parts of Europe, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
100
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 23 publications
10
100
1
4
Order By: Relevance
“…We found that the impact of extreme temperatures on mortality in Italy was quite limited, with the exception of the 2016/17 season. Despite this impact of extreme low temperatures, most of the excess death rate registered in 2016/17 is attributable to influenza, confirming other observations recorded in Europe (Nielsen et al, 2019). Nevertheless, this is the first study reporting the effect of temperatures on mortality in Italy, and we acknowledge that this association has to be further investigated, also analyzing this factor at sub-national level.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the impact of extreme temperatures on mortality in Italy was quite limited, with the exception of the 2016/17 season. Despite this impact of extreme low temperatures, most of the excess death rate registered in 2016/17 is attributable to influenza, confirming other observations recorded in Europe (Nielsen et al, 2019). Nevertheless, this is the first study reporting the effect of temperatures on mortality in Italy, and we acknowledge that this association has to be further investigated, also analyzing this factor at sub-national level.…”
Section: Discussionsupporting
confidence: 87%
“…As previously reported, influenza A(H3N2)-dominant epidemics have a considerable impact on mortality, with highest excess mortality attributable to influenza occurring mainly in older adults (12)(13)(14)30,31). In addition, a study suggests that influenza B might also be more of a concern in terms of excess mortality in the influenza season 2017-18 (32). However, many of these deaths might have occurred in older persons who have a cascade of illness after an influenza infection, and influenza in older patients might not have a typical clinical profile.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, influenza B virus circulates every year and often in significant numbers. In a study of hospitalized adults in the United States, influenza B caused similar severity to influenza A, and it has been shown to cause fatal illness in persons of all ages . Primarily trivalent influenza vaccines are used in Europe; however, given that both B lineages might circulate every year, recently reporting entities have begun to examine the cost‐effectiveness of using quadrivalent vaccine .…”
Section: Discussionmentioning
confidence: 99%